Geology and structure of the Sundarijal-Melamchi area, central Nepal - Dhital, Megh Raj; Sunuwar, Subas Chandra; Shrestha, Rajendra (Journal of Nepal Geological Society, 2002)
In the Sundarijal- Melamchi area, the following lithological units arc identified based on detailed field mapping: the Talamarang Formation (dark grey feldspathic schist and banded gneiss with garnet and kyanite), Gyalthum Formation (thin- to thick banded, light grey to grey, laminated quartzite with mica partings and bands of feldspathic schist. garnetiferous schist, and gneiss), Bolde Quartzite (grey to light grey, very thick-banded, massive quartzite with mica parting and schist bands containing sillimanite). Timbu Formation (light grey to dark grey, intensely deformed and folded quartzite, gneiss, and migmatite with abundant sillimanite), and Golphu Formation (grey to dark grey feldspathic schist and banded gneiss with large pegmatite veins) from bottom to top, respectively. The Main Central Thrust (MCT) crosses the Indrawati River north of Majhitar and continues towards the Dhand Khola to SE and joins with the Mahabharat Thrust. It is moderately steep and dips essentially due NW. The footwall of the MCT is made up mainly of slate and phyllite and the grade of metamorphism is quite low in comparison with that of the hanging wall. The inverted metamorphism is conspicuous in the hanging wall of the MCT, where at first garnet schist is observed, which passes rapidly upwards to kyanite schist and then to sillimanite-bearing schist, gneiss, and migmatite. Augen and banded gneisses invade the upper part of the northern limb and most of the southern limb of the Patibhanjyang Anticline. Apparently, the Sheopuri Injection Gneiss Zone is a continuation of the Kutumsang Gneiss Zone in the north, and the rocks were folded after the emplacement of the injection gneisses.